Activation of Rac1-Mineralocorticoid Receptor Pathway Contributes to Renal Injury in Salt-Loaded db/db Mice. Issue 1 (1st June 2021) - Hirohama, Daigoro; Nishimoto, Mitsuhiro; Ayuzawa, Nobuhiro; Kawarazaki, Wakako; Fujii, Wataru; Oba, Shigeyoshi; Shibata, Shigeru; Marumo, Takeshi; Fujita, Toshiro
Abstract : Supplemental Digital Content is available in the text. Abstract : The progression of diabetic kidney disease (DKD), a leading cause of end-stage kidney disease, involves mineralocorticoid receptor (MR) activation. We previously identified crosstalk between the small guanosine triphosphatase (GTPase) RAS-related C3 botulinus toxin substrate 1 (Rac1) and MR, but the role of Rac1-MR pathway activation in the progression of DKD is not clear. We performed uninephrectomy on type 2 diabetic mouse models, db/db (UNx-high salt [HS] db/db ), and their lean control, db/m (UNx-HS db/m ), at 4-week postpartum, and fed them a high-salt diet for 10 weeks. To evaluate the involvement of the Rac1-MR pathway in the DKD progression, we investigated the effects of the nonsteroidal MR antagonist, finerenone, and the Rac1 inhibitor, NSC23766, on blood pressure and glomerular injury in UNx-HS db/db mice. UNx-HS db/db mice with hyperaldosteronism showed hypertension and hypokalemia with increased cleaved α-epithelial sodium channel expressions and massive albuminuria, accompanied by glomerular injury with nodular lesions, which is a characteristic finding in human diabetic nephropathy. Expressions of active Rac1 and serum-and glucocorticoid-induced protein kinase 1 (Sgk1), a downstream molecule of MR signaling, in the renal cortex and isolated glomeruli, significantly elevated in UNx-HS db/db mice, associated with intense staining of active Rac1 in glomerular podocytes, but both hypertension and renal injury were ameliorated by NSC23766 and finerenone, associated with Sgk1 inhibition, suggesting that Rac1-MR activation contributes to hypertension and podocyte injury. In conclusion, salt-induced activation of Rac1-MR pathway in distal tubules and glomeruli is involved in DKD progression through hypertension and glomerular injury, respectively. This finding highlights MR antagonism along with Rac1 inhibition as a novel strategy for DKD treatment.